DECORATIVE DESIGNS OF SPHEROCONICAL VESSELS: THE EXAMPLE OF THE OLD TERMIZ MONUMENT (American Journal of Research in Humanities and Social Sciences, 2026)
Among more than 50 monuments in Central Asia, more than 300 “simobko‘zacha” - spheroconical vessels - were discovered during archaeological research conducted in various years in Old Termez. Spherocones - are vessels from the Middle Ages, made mainly by potters, distinguished from other ceramic products by their sturdy, thick-walled, small rim, narrow neck, variously shaped belly, and often conical bottom. These types of finds are significant because they are widespread in the Muslim East. Debates about these findings have been ongoing among scientists and enthusiasts since the early 19th century. The main cause of the controversy is the question of what the function of the mercury jars is.Spheroconical vessels found at the ancient Termez monument are currently kept in the Medieval Fund of the Termez Archaeological Museum. They have types that differ from each other in morphological structure, capacity, and decoration. This article discusses the decorations and their types found on Old Termez spheroconical vessels.The ornaments were applied to the surface of the dishes before firing, using stamps or pointed tools. Each ornament has its own meaning.